The butter battle book - Enterprises, Seuss (Random House, 1984)
A cautionary Cold War tale (first told by Dr. Seuss back in 1984), The Butter Battle Book still has a lot to teach about intolerance and how tit-for-tat violence can quickly get out of hand. Explaining the very serious differences between the Zooks and the Yooks, a Zook grandpa tells his grandchild the unspeakable truth: "It's high time that you knew of the terribly horrible thing that Zooks do. In every Zook house and every Zook town every Zook eats his bread with the butter side down!" He then recalls his days with the Zook-Watching Border Patrol, as he gave any Zook who dared come close "a twitch with my tough-tufted prickley Snick-Berry Switch." But when the Zooks fought back, the switches gave way to Triple-Sling Jiggers, then Jigger-Rock Snatchems--even a Kick-a-Poo Kid that was "loaded with powerful Poo-a-Doo Powder and ants' eggs and bees' legs and dried-fried clam chowder."